Maze master - Gear, Kathleen O'Neal (St. Martin's Press, 2018)
LucentB is a retrovirus that<U+2019>s inevitable, unstoppable, and utterly catastrophic for humanity. The US government believes the only person who can find the cure is the geneticist who tried to warn them about it and then disappeared: James Hakari. They assign the task of finding him to his former student Anna Asher, who in turn recruits paleographer and religious studies scholar Dr. Martin Nadai. The brilliant but insane geneticist is leaving clues for Anna and Martin to follow, showing he<U+2019>s truly earned his students<U+2019> nickname for him: the Maze Master. The search takes Anna and Martin around the world and into a warzone they never imagined. Maze Master's LucentB is based off of the real retrovirus HERV-K, which has caused several plagues over the past 75,000 years, almost wiping out Neandertals 50,000 years ago, and maybe 30,000 years ago. Modern geneticists consider HERV-K not to be extinct, but rather to be waiting for some trigger to come alive again.